Interaction between soft rocks and water and its application to engineering. Issue 5 (October 2020) - Zeng, Qinghe; Ming, Weihua; Wang, Xiangdong; Liu, Zhen; Tan, Xiangshao; Zhou, Cuiyng
Abstract: The interaction between soft rocks and water is a frontal project in the field of geotechnical engineering. This study constructs a time-effect model on the interaction between soft rocks and water by experimenting on the interaction and physical-mechanic of soft rocks, such as silty mudstone, argillaceous siltstone, and carbonaceous mudstone, which are sampled from a water supply project in South China. It also investigates the chemical mechanism of softening when soft rocks interact with water. Thus, the study not only builds a foundation for the theme of water–rock interaction but also provides effective guidance for the construction of priority projects.